Spindle movement and checkpoint control during mitosis in yeast - Cooper, John (Henry Stewart Talks, 2009)
Cell cycle checkpoints for partitioning the genome, Budding yeast as a model system for the study of genome distribution, How nuclei are segregated in yeast, Evidence for a spindle position checkpoint, Model for checkpoint based on Tem1, Movie assay for checkpoint, Search for upstream inputs, Screen for checkpoint mutants, Septins dual role in checkpoint, Inputs to Lte1, Bud6 and microtubule capture, Potential pathway for Bud6, Bud6 and microtubule-binding proteins, Overexpression analysis, Inhibition of Lte1 in the cold